DESCRIPTION OF MODERN WOUND CARE USING RED FRUIT OINTMENT DRESING FOR Mr. S WITH DIABETICT ULCER IN GELANG VILLAGE RAKIT DISTRICT - Meli Nur Azizah; Sudiarto; Eko Julianto (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Background: Diabetic ulcers are a chronic complication frequently experienced by individuals with diabetes mellitus and significantly contribute to morbidity, mortality, and lower extremity amputation rates. Effective wound management is key to preventing further complications. Modern dressings based on the moist wound healing principle have been proven more effective than conventional methods, as they maintain wound moisture and support tissue regeneration. Objective: To describe the treatment of diabetic ulcers using the modern dressing method with red fruit (Pandanus conoideus Lamk) ointment in Gelang Village, Rakit District. Methods : This study used a descriptive case study approach involving one diabetic ulcer patient who met the inclusion criteria. Wound care was performed every two days for 14 days using modern dressing and red fruit ointment. Data were collected through observation, interviews, and documentation. Results: There was an improvement in wound conditions after the application of red fruit ointment, marked by an increase in granulation tissue and a decrease in necrotic tissue. The active ingredients in the ointment such as β-carotene, tocopherol, oleic acid, and linoleic acid have antioxidant and anti-inflammatory effects that accelerate the healing process. Conclusion: Modern dressing with red fruit ointment is effective in accelerating the healing process of diabetic ulcers and can serve as an alternative topical therapy to support optimal wound recovery